Changes in the morphology and cell ultrastructure of a microalgal community exposed to a commercial glyphosate formulation and a toxigenic cyanobacterium - Hernández-García, Claudia Ivette; Martínez-Jerónimo, Fernando (Frontiers in Microbiology, 2023)
Human activities significantly influence the health of aquatic ecosystems because many noxious chemical wastes are discharged into freshwater bodies. Intensive agriculture contributes to the deterioration by providing indirectly fertilizers, pesticides, and other agrochemicals that affect the aquatic biota. Glyphosate is one of the most used herbicides worldwide, and microalgae are particularly sensitive to its formulation, inducing displacement of some green microalgae from the phytoplankton that leads to alterations in the floristic composition, which fosters the abundance of cyanobacteria, some of which can be toxigenic. The combination of chemical stressors such as glyphosate and biological ones, like cyanotoxins and other secondary metabolites of cyanobacteria, could induce a combined effect potentially more noxious to microalgae, affecting not only their growth but also their physiology and morphology. In this study, we evaluated the combined effect of glyphosate (Faena®) and a toxigenic cyanobacterium on the morphology and ultrastructure of microalgae in an experimental phytoplankton community. For this purpose, Microcystis aeruginosa (a cosmopolitan cyanobacterium that forms harmful blooms) and the microalgae Ankistrodesmus falcatus, Chlorella vulgaris, Pseudokirchneriella subcapitata, and Scenedesmus incrassatulus were cultivated, individually and jointly, exposing them to sub-inhibitory concentrations of glyphosate (IC10, IC20, and IC40). Effects were evaluated through scanning electron (SEM) and transmission electron (TEM) microscopy. Exposure to Faena® produced alterations in the external morphology and ultrastructure of microalgae both individually and in combined cultures. SEM evidenced the loss of the typical shape and integrity of the cell wall and an increase in the biovolume. TEM revealed reduction and disorganization of the chloroplast, variation in starch and polyphosphate granules, formation of vesicles and vacuoles, cytoplasm degradation, and cell wall continuity loss. The presence of M. aeruginosa was, for microalgae, an additional stress factor adding to the chemical stress produced by Faena®, increasing the damage in their morphology and ultrastructure. These results alert to the effects that can be caused by glyphosate and the presence of toxigenic bacteria on the algal phytoplankton in contaminated and anthropic and eutrophic freshwater ecosystems.